2022
DOI: 10.3390/ijerph19031381
|View full text |Cite
|
Sign up to set email alerts
|

Medical Waste from COVID-19 Pandemic—A Systematic Review of Management and Environmental Impacts in Australia

Abstract: The coronavirus (COVID-19) pandemic has created a global medical emergency. The unforeseen occurrence of a pandemic of this magnitude has resulted in overwhelming levels of medical waste and raises questions about management and disposal practices, and environmental impacts. The amount of medical waste generated from COVID-19 since the outbreak is estimated to be 2.6 million tons/day worldwide. In Australia, heaps of single-use gowns, facemasks/face shields, aprons, gloves, goggles, sanitizers, sharps, and syr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 65 publications
(206 reference statements)
0
24
0
11
Order By: Relevance
“…Social distancing and the change in lifestyle in general during the pandemic were also reflected in an increase in the use of disposable plastics (Haque & Fan, 2022 ; Igalavithana et al, 2022 ), as well as in food waste mainly in large cities (Çavuş et al, 2022 ; Iranmanesh et al, 2022 ). In developed countries, different strategies were implemented to deal with these new amounts of waste, new waste treatment facilities were installed, and policies were implemented in favor of prioritizing the treatment of medical waste (Andeobu et al, 2022 ). However, in underdeveloped countries there was no planning that could mitigate the problem represented by these new rates of generation of toxic waste; therefore, a large part of the waste generated ended up in open-air landfills, which represents great health and environmental risk for the region (Masud et al, 2023 ).…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…Social distancing and the change in lifestyle in general during the pandemic were also reflected in an increase in the use of disposable plastics (Haque & Fan, 2022 ; Igalavithana et al, 2022 ), as well as in food waste mainly in large cities (Çavuş et al, 2022 ; Iranmanesh et al, 2022 ). In developed countries, different strategies were implemented to deal with these new amounts of waste, new waste treatment facilities were installed, and policies were implemented in favor of prioritizing the treatment of medical waste (Andeobu et al, 2022 ). However, in underdeveloped countries there was no planning that could mitigate the problem represented by these new rates of generation of toxic waste; therefore, a large part of the waste generated ended up in open-air landfills, which represents great health and environmental risk for the region (Masud et al, 2023 ).…”
Section: Problem Statementmentioning
confidence: 99%
“…In recent studies, it has not been possible to determine if infectious waste plays a critical role in the distribution of the virus; however, the deposition of different medical residues in the water and soil ecosystem can cause microbial transformations, which represents a potential threat to the public health system (Ekhaise et al, 2023 ). For this reason, the enormous amounts of waste generated during the pandemic make processing this waste a priority (Andeobu et al, 2022 ; Dharmaraj et al, 2021 ). To minimize the environmental and social impact in the short and long term, implementing efficient waste management strategies is necessary to reduce the long-term effects that the pandemic may generate, solving this challenge and creating technological techniques and knowledge will enable the safe treatment of municipal waste in the current pandemic, and above all to generate prevention strategies in the face of the possibility of future pandemics (Skrzyniarz et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated daily plastic waste generated rounds about 1.6 million tons from 3.4 billion discarded single-use facemasks ( Benson et al., 2021a ). Alongside a massive surge in plastic pollution, the PPE wastes may also become disease vectors introducing new pathogenic virus or bacteria ( Noman et al., 2021 ; and Andeobu et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, since protective measures such as mask wearing, traffic restrictions, social distancing, and home isolation have been globally implemented to reduce the spread of the COVID-19 [18], it has been found that waste has increased in numerous countries due to the intensification of said measures [19]. Moreover, several studies have also shown that medical waste has increased significantly due to the COVID-19 pandemic [20,21]. This is mainly to sustain the enormous demand for personal protective equipment which includes face masks, gloves, gowns, etc.…”
Section: Introductionmentioning
confidence: 99%